Strong indirect coupling between graphene-based mechanical resonators via a phonon cavity - Gang Luo (Nature Portfolio, 2018)
Non-neighbouring mechanical resonators can interact via indirect coupling. Here, the authors leverage a resonant phonon cavity in a graphene-based electromechanical system to demonstrate strong indirect coupling between separated mechanical resonators.